Europe After Wyclif - Hornbeck II, J. Patrick (Fordham Series in Medieval Studies, 2016)
This volume brings together scholarship that discusses late-medieval religious controversy on a pan-European scale, with particular attention to developments in England, Bohemia, and at the general councils of the fifteenth century. Controversies such as those that developed in England and Bohemia have received ample attention for decades, and recent scholarship has introduced valuable perspectives and findings to our knowledge of these aspects of European religion, literature, history, and thought. Yet until recently, scholars working on these controversies have tended to work in regional isolation, a practice that has given rise to the impression that the controversies were more or less insular, their significance measured in terms of their local or regional influence.